Utilisation of the Tafsir Learning Method to Improve Quranic Comprehension Among Students at Madrasah Faqihul Ilmi Makassar - Muhammadong Muhammadong; Nurhilaliyah Nurhilaliyah; Sitti Muthmainnah; Khaerunnisa Khaerunnisa (JUKEMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
A solid grasp of the Qur'an is an essential basis for cultivating pupils' character and intellect. Some students of Madrasah Faqihul Ilmi Makassar still have trouble fully and contextually understanding the meanings of Qur'anic passages. The goal of this community service programme is to help students understand the Qur'an better by using a hands-on and interactive tafsir learning technique. The programme is for all middle school students who are taking Qur'an and Tafsir classes. Direct instruction, group discussions, step-by-step verse interpretation exercises, Questions and Answers (Q&A) activities, and simulations are all ways to put Qur'anic values into practice in everyday life. We evaluate by watching how well students participate, doing exercises to clarify the meanings of verses, and reflecting on what they learned each day. The results reveal that students are more interested in learning, better at explaining tafsir, and more aware of how to use Qur'anic values at home and in school. This programme is efficient at improving understanding of the Qur'an, increasing enthusiasm in learning, and developing religious character. In conclusion, using the tafsir learning method in community service projects can be a useful and effective way to help students at Madrasah Faqihul Ilmi Makassar improve their religious skills.